ANALISIS PENGARUH TENAGA KERJA DAN MODAL MANUSIA TERHADAP PERTUMBUHAN EKONOMI DALAM PENGENTASAN KEMISKINAN - Ghina Nabila Ali (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Economic development in the traditional economy is only measured using GDP growth, both in aggregate and per capita. Further increases in GDP will create the necessary conditions for a more equitable distribution of economic and social growth results. However, orientation only to economic growth in building national economy has drawn considerable criticisms. From this point, new economic views have emerged. According to Todaro (2006), the main objective of the new views is GDP growth with simultaneous improvements in poverty alleviation and inequality reduction. High economic growth is often followed by high poverty. Therefore, sustainable economic growth, known as the inclusive growth, is required. In Indonesia, there are still provinces that have not achieved a good level of inclusiveness, one of which is East Java. The rate of its economic growth is very high, but the number of poor people in the area is above the national average. This study aims to analyze the effect of labor and human capital on economic growth in poverty alleviation in East Java using the case study method of 38 regencies and cities during the 2011-2020 period. The panel data was analyzed simultaneously in E-views. This study finds that labor does not affect economic growth, but human capital described by health and education affects economic growth. Further, negative economic growth positively and significantly affect poverty, which means that increasing human capital has a good impact on economic growth and will further reduce poverty.